Le procedure per le nomine dei vescovi nella Chiesa latina: tra informazione e preferenza (Stato, Chiese e pluralismo confessionale, 2017)
Contributo sottoposto a valutazioneSOMMARIO: 1. Introduzione - 2. Il ruolo dei singoli vescovi - 3. Alcune dinamiche del contributo dei vescovi in assemblea - 4. Sui titoli di partecipazione di fedeli non vescovi alle procedure - 5. L’operato del legato pontificio come fulcro della singola nomina - 6. La Sede apostolica come istanza di decisione - 7. Conclusione.The Legal Procedures for the Appointment of Bishops in Latin Church: Information and PreferenceABSTRACT :The article focuses on the procedures for appointment of bishops in Latin Church from two specific outlooks. The first one regards the circulation of information fostered by procedures. Rather than discussing about whom is given the juridical power to appoint bishops, the procedures are analysed from the point of view of the information the agents are incentivated to provide in order to form the final decision. Procedures aim as well to a special kind of information, namely “preference”, of some persons or groups of persons entitled to shape the administrative act of appointment. The perspective of providing information and preference in order to foster a more prudent resolution is useful to understand some subtle dimensions of current procedures but also to suggest improvements. The second outlook is related to the title of participation of five different kinds of subjects that take part in legal procedures: single bishop, provincial bishops’ assembly, faithful (who are not bishops), pontifical legate and Holy See. The juridical ground for each of these subjects’ involvement in the procedures along with the relationships between them, outline the profile of the appointment system and its dynamics. The analysis of some aspects of those grounds and relationships provides a wider view of the purposes and limits of the procedures themselves.